FAT AND WATER DISTRIBUTION PATTERNS IN THE FLESH OF THE COMMON CAT - FISH WALLAGO ATTU (BL.& SCHN.) - JAFRI, A K (Fishery Technology, 2016)
The quantitative distributional pattern of fat and water hasbeen studied in the flesh of the various zones corresponding tothe dorsal and ventral regions of the body of a common cat-fish,W. attu. The ventral aspect of the body showed more accumulationof fat than the dorsal aspect, The fat content in the ventralregion also exhibited an increase from the anterior to theposterior zones. In the dorsal region, however, the back portion ofthe body, behind the dorsal fin, generally possessed low fat content.On an average, the highest fat accumulation was observedin the caudal peduncle region. The distribution of water followedan almost opposite pattern of distribution, indicating an inverserelationship with fat.